Ritual worship of the great goddess : the liturgy of the Durgā Pūjā with interpretations - Rodrigues, Hillary, 1953- (McGill studies in the history of religions., 2003)
"During a nine-day period every autumn, Hindus in India and throughout the world worship the Great Goddess, Durga - the formidable deity who is loved like a mother. One of the most dramatic and popular of these celebrations is the Durga Puja, a rite noted for its visual pageantry, ritual complexity, and communal participation. In this book, Hillary Peter Rodrigues describes the Bengali style of Durga Puja practiced in the sacred city of Banaras from beginning to end. A romanization of the Sanskrit litany is included along with an English translation." "In addition to the liturgical description, Rodrigues provides information on the rite's component elements and mythic aspects. There are interpretive sections on puja, the Great Goddess, women's roles in the ritual, and the socio-cultural functions of the ritual. Rodrigues maintains that the Durga Puja is a rite of cosmic rejuvenation, of empowerment at both the personal and social levels, and a rite that orchestrates manifestations of the feminine, both Divine and human."--Jacket